2020
DOI: 10.3389/fonc.2020.595466
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Radiation Resistance of Non-Small Cell Lung Cancer by Dihydroartemisinin Through Abrogating Immunity Escaping and Promoting Radiation Sensitivity by Inhibiting PD-L1 Expression

Abstract: Radiation resistance is linked to immune escaping and radiation sensitivity. In this study, we found that the PD-L1 expressions of non-killed tumor cells in NSCLC were enhanced after radiotherapy, and dihydroartemisinin (DHA) could synergistically enhance the antitumor effect of radiotherapy in NSCLC. A total of 48 NSCLC patients with sufficient tumor tissues for further analyses were enrolled. The PD-L1 expressions of NSCLC were evaluated by immunohistochemistry. Cell apoptosis was measured by flow cytometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
(70 reference statements)
0
27
0
Order By: Relevance
“…Further, Zhang et al confirm that in NSCLC, on the one hand, DHA reduces the expression of PD-L1 on tumor cells by inhibiting the expression of TGF-b and PI3K/Akt and STAT3 signaling pathways, thus impairs tumor immune escape. On the other hand, DHA increases the sensitivity of NSCLC to radiotherapy by regulating the expression of EMT-associated proteins (79). In summary, DHA promotes T-cell-centered anti-tumor immunity by reducing the secretion of immunosuppressive cytokines and suppressing the number and function of immunosuppressive cells.…”
Section: Enhance Anti-tumor Immunitymentioning
confidence: 95%
“…Further, Zhang et al confirm that in NSCLC, on the one hand, DHA reduces the expression of PD-L1 on tumor cells by inhibiting the expression of TGF-b and PI3K/Akt and STAT3 signaling pathways, thus impairs tumor immune escape. On the other hand, DHA increases the sensitivity of NSCLC to radiotherapy by regulating the expression of EMT-associated proteins (79). In summary, DHA promotes T-cell-centered anti-tumor immunity by reducing the secretion of immunosuppressive cytokines and suppressing the number and function of immunosuppressive cells.…”
Section: Enhance Anti-tumor Immunitymentioning
confidence: 95%
“…Artemisinin is mainly used in the treatment of malaria. Our patient was treated with artemether and dihydroartemisinin because the effect of dihydroartemisinin is 5 times more potent against malaria than artemisinin[ 3 ]. She subsequently took oral dihydroartemisinin and piperaquine phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that DHA inhibited HepG2(Hao et al 2021) and HepG2215 cells (Shi et al 2019). Meanwhile, some studies suggested that DHA downregulated PD-L1 expression in non-small cell lung cancer (Zhang et al 2020). Interestingly, DHA decreased YAP1 in tumor tissues but increased YAP1 in para-tumor, leading to the increased ratio of YAP1, suggesting the competitive advantage of para-tumor tissues, which appears to eliminate liver tumor cells in mice (Moya et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroartemisinin (DHA), approved by FDA as an anti-malarial drug, is a derivative of artemisinin extracted from artemisia annua . In addition, DHA inhibited the expression of PD-L1 by inhibiting TGF-ÎČ, STAT3 and PI3K/AKT signaling pathways in non-small cell lung cancer (Zhang et al 2020). Our previous study showed that DHA inhibited cell proliferation in human hepatocellular carcinoma HepG2215 cells (Shi et al 2019) and promoted p-STAT3 (Y705) nuclear localization in human tongue squamous cell carcinoma Cal-27 cells (Shi et al 2017).…”
Section: Introductionmentioning
confidence: 99%